2018
DOI: 10.1634/theoncologist.2018-0084
|View full text |Cite
|
Sign up to set email alerts
|

FDA Approval Summary: Atezolizumab or Pembrolizumab for the Treatment of Patients with Advanced Urothelial Carcinoma Ineligible for Cisplatin-Containing Chemotherapy

Abstract: The U.S. Food and Drug Administration (FDA) granted accelerated approval to atezolizumab and pembrolizumab in April and May 2017, respectively, for the treatment of patients with locally advanced or metastatic urothelial carcinoma who are not eligible for cisplatin‐containing chemotherapy. These approvals were based on efficacy and safety data demonstrated in the two single‐arm trials, IMvigor210 (atezolizumab) and KEYNOTE‐052 (pembrolizumab). The primary endpoint, confirmed objective response rate, was 23.5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
111
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(126 citation statements)
references
References 13 publications
(17 reference statements)
0
111
0
3
Order By: Relevance
“…Patienten mit einer niedrigen PD-L1-Expression (PD-L1-Expression < 5 % bzw. CPS [combined positivity score] < 10), die mit einem Immuncheckpoint-Inhibitor behandelt wurden, wiesen im Vergleich zu Patienten mit einer Platin-basierten Erstlinientherapie ein schlechteres Gesamtüberleben auf [27,28]. Auch in 2 Phase-II-Studien zum Einsatz von Immuncheckpoint-Inhibitoren in der neoadjuvanten Therapiesituation konnte das Tumoransprechen mit dem PD-L1-Status korreliert werden.…”
Section: Immun-checkpoint-inhibitionunclassified
“…Patienten mit einer niedrigen PD-L1-Expression (PD-L1-Expression < 5 % bzw. CPS [combined positivity score] < 10), die mit einem Immuncheckpoint-Inhibitor behandelt wurden, wiesen im Vergleich zu Patienten mit einer Platin-basierten Erstlinientherapie ein schlechteres Gesamtüberleben auf [27,28]. Auch in 2 Phase-II-Studien zum Einsatz von Immuncheckpoint-Inhibitoren in der neoadjuvanten Therapiesituation konnte das Tumoransprechen mit dem PD-L1-Status korreliert werden.…”
Section: Immun-checkpoint-inhibitionunclassified
“…The use of such agents has resulted in prolonged disease‐free remission and overall survival in malignancies that were previously fatal (Freeman et al, ; Hanahan & Weinberg, ; Iwai et al, ). To date, PD‐1 inhibitors have been approved for the treatment of advanced and refractory cancers including melanoma, non‐small‐cell lung cancer, renal cell carcinoma, head and neck cancer, Hodgkin lymphoma, urothelial cancer, cervical cancer, and gastric cancer; their use is expected to continue to increase with additional approvals (Chen et al, ; Chung et al, ; Fashoyin‐Aje et al, ; Finkelmeier, Waidmann, & Trojan, ; Hauschild & Schadendorf, ; Hodi et al, ; Larkins et al, ; Printz, ; Suzman et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, PD-1 inhibitors have been approved for the treatment of advanced and refractory cancers including melanoma, non-smallcell lung cancer, renal cell carcinoma, head and neck cancer, Hodgkin lymphoma, urothelial cancer, cervical cancer, and gastric cancer; their use is expected to continue to increase with additional approvals Chung et al, 2019;Fashoyin-Aje et al, 2019;Finkelmeier, Waidmann, & Trojan, 2018;Hauschild & Schadendorf, 2016;Hodi et al, 2010;Larkins et al, 2017;Printz, 2017;Suzman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the past, more and more genetic and epigenetic markers could show its predictive and/or prognostic value regarding overall survival and even cancer specific survival. As an example of how a tumor marker can predict therapeutic success, the results of the phase 2 KEYNOTE-052 (NCT02335424) study showed how a marker could influence therapeutic decisions on one hand, and that negative marker results were also not a certain predictor of therapeutic success [22]. PD-L1 positive is defined as a combined positive score (CPS) ≥10.…”
mentioning
confidence: 99%